Удосконалення транспортно – логістичної системи підприємства - Мурований, Ігор (ТзОВ «Галицька видавнича спілка», 2021)
The article considers three approaches to the content of the concept of "transport and logistics system of the enterprise": the process of optimizing transport and logistics flows; a set of logistics functions; a set of interconnected elements.
Improvement of the transport and logistics system of the enterprise
Keywords: 656.13